Efficacy and safety of switching to pasireotide in acromegaly patients controlled with pegvisomant and somatostatin analogues: PAPE extension study. Issue 5 (November 2018) - Muhammad, Ammar; Coopmans, Eva C; Delhanty, Patric J D; Dallenga, Alof H G; Haitsma, Iain K; Janssen, Joseph A M J L; van der Lely, Aart J; Neggers, Sebastian J C M M
Abstract : Objective: To assess the efficacy and safety after 48 weeks of treatment with pasireotide long-acting-release (PAS-LAR) alone or in combination with pegvisomant in patients with acromegaly. In addition, we assessed the relation between insulin secretion and pasireotide-induced hyperglycemia. Design: The PAPE extension study is a prospective follow-up study until 48 weeks after the core study of 24 weeks. Methods: Fifty-nine out of 61 patients entered the extension study. Efficacy was defined as the percentage of patients achieving IGF-I normalization (≤1.2× the upper limit of normal (ULN)) at 48 weeks through protocol-based adjustment of pegvisomant and PAS-LAR doses. At baseline, insulin secretion was assessed by an oral glucose tolerance test (OGTT). Results: At the end of the study, median IGF-I was 0.98× ULN, and 77% of patients achieved normal IGF-I levels with a mean pegvisomant dose of 64 mg/week, and an overall cumulative pegvisomant dose reduction of 52%. Frequency of diabetes mellitus increased from 68% at 24 weeks to 77% at 48 weeks, and nine patients discontinued PAS-LAR treatment, mainly because of severe hyperglycemia. Pasireotide-induced hyperglycemia was inversely correlated with baseline insulin secretion ( r = −0.37, P < 0.005). Conclusions: PAS-LAR normalizes IGF-I levels in most acromegaly patients, with a 50% pegvisomant-sparing effect. However, PAS-LAR treatment coincided with a high incidence of diabetes mellitus. The risk for developing diabetes during PAS-LAR treatment seems inversely related to insulin secretion at baseline.